Cultural heritage and disaster management - Raimon, S. (Thiruvananthapuram : Kerala State Archives Dept., 2006)
Contributed papers presented at the National Seminar on Disaster Management held in 2003 at Trivandrum; co-organized by National Museum Institute, New Delhi.
Includes bibliographical references.
Keywords: Cultural property -- India -- Congresses; Emergency management -- India -- Congresses